Patients with acute intracerebral hemorrhage and severe symptoms are highly sensitive to prehospital delay. A subgroup analysis from the RESIST and TRIAGE-STROKE trials - Behrndtz, Anne; Simonsen, Claus Z.; Valentin, Jan B.; Andersen, Grethe; Blauenfeldt, Rolf A. (Frontiers in Stroke, 2024)
Background: Patients with a positive prehospital stroke severity score and underlying intracerebral hemorrhage (ICH) may be harmed by longer onset to admission times. We aimed to investigate the interaction between ICH severity and time from onset to admission on functional outcome.Methods: This is an individual patient data analysis with data from two randomized prehospital stroke trials (RESIST and TRIAGE-STROKE) using the same prehospital stroke scale. Patients were stratified according to a presence of a positive stroke severity score. They were grouped into early arrivers (admitted less than 90 minutes from onset) and late arrivers ( ≥90 minutes after onset). The primary outcome was shift towards a better functional outcome on the modified Rankin Scale (mRS).Results: A total of 212 patients had ICH. A positive stroke severity score was seen in 123 of these patients. Patients with ICH and a positive prehospital stroke severity score had a significantly worse outcome if 90 minutes or later at the hospital (aOR: 2.02, 95%CI; 1.01 to 4.12). This difference was not seen in patients without a positive severity score (adjusted odds ratio [aOR]: 0.50, 95%CI; 0.22 to 1.14). Patients with a positive score had also an increasing risk of death or severe dependency (mRS of 5-6) of 9.1%-points (95%CI:-1.6% to19.8%) per hour if they were diagnosed with ICH.Longer onset to admission time was harmful for patients with ICH and a positive prehospital stroke severity score.